The synergistic interaction of systemic inflammation, dysbiosis and antimicrobial resistance promotes growth restriction in children with acute severe malnutrition: An emphasis on Escherichia coli - Arredondo-Hernandez, Rene; Siebe, Christina; Castillo-Rojas, Gonzalo; Ponce de León, Samuel; López-Vidal, Yolanda (Frontiers in Antibiotics, 2022)
A healthy development is denied to millions of children worldwide as harsh life conditions manifest themselves in an altered inflammation-prone microbiome crosstalk environment. Keynote of this tragedy is that insufficient nutritious amino acid blocks lipids-intake to sustain diverse microbiota, and promotes the generalist strategy followed by Escherichia coli -besides other proteobacteria- of shifting gut metabolism, subverting the site specificity of first immune reaction. Furthermore, it could be hypothesized that selective success lies in their ability to induce inflammation, since this phenomenon also fuels horizontal gene transfer (HGT). In this review, we dilucidate how immune mechanisms of environmental enteric dysfunction affect overgrowth restriction, infectious morbidity rate, and acquired lifelong risks among severe acute malnourished children. Also, despite acknowledging complexities of antimicrobial resistant enrichment, we explore and speculate over the links between virulence regulation and HGT as an indissociable part in the quest for new inflammatory niches by open genome bacteria, particularly when both collide in the most vulnerable.